Altered inflammatory activity associated with reduced hippocampal volume and more severe posttraumatic stress symptoms in Gulf War veterans. (January 2015) - O'Donovan, Aoife; Chao, Linda L.; Paulson, Jennifer; Samuelson, Kristin W.; Shigenaga, Judy K.; Grunfeld, Carl; Weiner, Mike W.; Neylan, Thomas C.
Highlights: Our sample includes veterans with and without posttraumatic stress disorder (PTSD). We examine if inflammatory markers are associated with hippocampal volume. Higher sTNF-RII, but not IL-6, was associated with reduced hippocampal volume. Neither current nor past PTSD diagnoses were associated with sTNF-RII or IL-6. More severe PTSD symptoms were associated with elevated sTNF-RII and lower IL-6. Summary: Background: Inflammation may reduce hippocampal volume by blocking neurogenesis and promoting neurodegeneration. Posttraumatic stress disorder (PTSD) has been linked with both elevated inflammation and reduced hippocampal volume. However, few studies have examined associations between inflammatory markers and hippocampal volume, and none have examined these associations in the context of PTSD. Methods: We measured levels of the inflammatory markers interleukin-6 (IL-6) and soluble receptor II for tumor necrosis factor (sTNF-RII) as well as hippocampal volume in 246 Gulf War veterans with and without current and past PTSD as assessed with the Clinician Administered PTSD Scale (CAPS). Enzyme-linked immunosorbent assays were used to measure inflammatory markers, and 1.5 Tesla magnetic resonance imaging (MRI) and Freesurfer version 4.5 were used to quantify hippocampal volume. Hierarchical linear regression and analysis of covariance models were used to examine if hippocampal volume and PTSD status would be associated with elevated levels of IL-6 and sTNF-RII. Results: Increased sTNF-RII, but not IL-6, was significantly associated with reduced hippocampal volume ( β = −0.14, p = 0.01). The relationship between sTNF-RII and hippocampal volume was independent of potential confounds and covariates, including PTSD status. Although we observed no PTSD diagnosis-related differences in either IL-6 or sTNF-RII, higher PTSD severity was associated with significantly increased sTNF-RII ( β = 0.24, p = 0.04) and reduced IL-6 levels ( β = −0.24, p = 0.04). Conclusions: Our results indicate that specific inflammatory proteins may be associated with brain structure and function as indexed by hippocampal volume and PTSD symptoms.